Peningkatan Pengetahuan Dan Efikasi Diri Melalui Promosi Kesehatan Tentang Pencegahan Kekambuhan Pasien Paska Pasung Pada Keluarga Di Kabupaten Klaten - Riyadi, Slamet; , Arif Widodo, A.Kep., M.Kes (2017)
Background. One of the National Development Program is the mental health field and its priority is to prevent the increasing mental health problems in the community. Indonesian government prohibits the stocks treatment for the patients with mental disorder. Even though, now adays the stocks treatment still commonly met in the community. By giving health promotion to the family is expected to improve the knowledge and efficacy of self-so that reduce the number of stocks treatment to prevent the recurrence of mental disorder patients. Objects and methods. Objects of this study are post stocks treatment mental disorder patient's families with total 34 samples are used. Study Design pre experiment with methods one group pretest posttest design with cross sectional study approach. Analysis of data used while to see the influence of health promotion to the familyknowledge and efficacy of self using T-test parametric results. There is differences knowledge before and after health promotion on prevention of recurrence with the P value 0,000 and there are differences in the efficacy of self before and after health promotion on prevention of recurrence with the P value 0,000. no significant differences between the change of knowledge and efficacy of self after giving health promotion on prevention of recurrence with the P value 0,000 on the post stocks treatment patient's family in Klaten district. Conclusion. Based on the study result there is an increase of knowledge and efficacy of self have the significant effect after objects given health promotion on prevention of recurrence of post stocks mental disorder patients.